União Monetária Europeia: reações assimétricas à luz da crise do euro - Pedroso, Ludmila Giuli (2015)
This paper summarizes the main Optimum Currency Area Theories (AMO), in order to use this branch of regional integration, to verify the configuration, in a cluster scenario, the euro area member countries during the period 2002-2013, from the perspective of macroeconomic imbalances factors, evidenced by the euro crisis, recent. Therefore, making use of statistical methods of multivariate analysis, and, factor analysis and cluster analysis were allowed to result in that during the period before the outbreak of the euro crisis had agreater concentration of countries in the first group, composed of countries more mature and more competitive economy. However, during the most turbulent crisis years, there is a greater amount of the groups formed by making the first less concentrated and dispersed in the composition of the other group. Only in the last two years of observation, 2012 and 2013, we find again a concentration of member countries in a group, then it is observed that in the years most critical crisis, show up macroeconomic disparities in the euro zone countries. Thus, the research contributes in order to verify, by means of multivariate analysis every year, over a period of time, and contrast with the reality that reaches the monetary union in Europe, to confirm that the disparities that existed before the outbreak of the crisis, and continue to exist between the members of the currency area. Confirming that the convergence criteria has not stopped economic disparities were reduced.